Anesthetic Sensitivity of the Gloeobacter violaceus Proton-Gated Ion Channel - Yun Weng; Liya Yang; Pierre‐Jean Corringer; James M. Sonner (2009)
In Brief A prokaryotic member of the γ-aminobutyric acid type A receptor superfamily (GLIC) was recently cloned from the cyanobacterium Gloeobacter violaceus, its function characterized, and its 3-dimensional x-ray diffraction crystal structure determined. We report its modulation by 9 anesthetics using 2-electrode voltage clamping in Xenopus laevis oocytes. Desflurane, halothane, isoflurane, sevoflurane, and propofol inhibited currents through GLIC at and below concentrations used clinically. Hill numbers averaged 0.3, indicating negative cooperativity or multiple sites or mechanisms of action. A 2-site model fit the data for desflurane and halothane better than a 1-site model. Xenon and etomidate modulated GLIC at or above clinical concentrations, with no cooperativity. Ethanol and nitrous oxide did not modulate GLIC at surgical anesthetic concentrations. These investigations lay the groundwork for further structural and functional studies of anesthetic actions on GLIC. Published ahead of print November 21, 2009